The European Union as a leader in international climate change politics - Connelly, James 1957-; Wurzel, Rüdiger 1961- (Routledge, 2011)
pt. 1. Introduction -- pt. 2. EU institutions -- pt. 3. The EU and its member states -- pt. 4. Civil society : business and environmental groups -- pt. 5. Europe and the wider world -- pt. 6. Conclusion.
Keywords: European Union; Climatic changes; Government policy; European Union countries; Environmental policy; Environmental policy / European Union countries; Climatic changes / Government policy / European Union countries; Aufsatzsammlung